Conduction systems for physalis production in southern Brazil Sistemas de condução para o cultivo de physalis no planalto catarinense - Muniz J.* (2011)
The culture of Physalis peruviana, the Solanaceae family, is still little explored in Brazil, but is a new option for diversification for small farmers, with good prospects for the domestic and international markets. It is an exotic fruit, belonging to the nightshade family and is known as 'camapum' and 'joá-de-capote', and can be confused with other species. It is a plant that can reach two meters in height when it is used an appropriate system, influencing plant development and quality of fruit produced. The objective was to evaluate the influence of four conduction systems in plants of Physalis in fruit production in two production cycles, during the years 2006-2007 and 2007-2008, in Lages, SC. It was evaluated the following conduction systems in "V", "X", simple and free espalier system. The experimental design was randomized blocks with four replicates and each experimental unit consisted of ten plants. It was observed that in two consecutive cycles, the "X" system showed the best results in most of the physico-chemical analysis, when compared with other conduction systems. It was conclude that the Physalis fits well the plateau region of Santa Catarina and that regardless of the conduction system used, the tutored plant under a conduction system had greater fruit weight, diameter and quality, thereby generating a result with higher commercial value.